2023
DOI: 10.3390/antiox12020361
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesized Zinc Oxide Nanoparticles Using Moringa olifera Ethanolic Extract Lessens Acrylamide-Induced Testicular Damage, Apoptosis, and Steroidogenesis-Related Gene Dysregulation in Adult Rats

Abstract: This study assessed the possible protective role of green synthesized zinc oxide nanoparticles using Moringa olifera leaf extract (MO-ZNPs) in acrylamide (ACR)-induced reproductive dysfunctions in male rats. ACR (20 mg/kg b.wt/day) and/or MO-ZNPs (10 mg/kg b.wt/day) were given orally by gastric gavage for 60 days. Then, sperm parameters; testicular enzymes; oxidative stress markers; reproductive hormones including testosterone, luteinizing hormone (LH)-estradiol, and follicle-stimulating hormone (FSH) concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 110 publications
3
6
0
Order By: Relevance
“…Previous studies have revealed excellent antioxidant activity of ZnO NPs and high ability to suppress the production of iNOS [ 63 ]. These results are supported by results of the present study which showed high antioxidant activity and high CAT levels in agreement with previous studies [ 30 , 63 , 64 ].…”
Section: Discussionsupporting
confidence: 94%
“…Previous studies have revealed excellent antioxidant activity of ZnO NPs and high ability to suppress the production of iNOS [ 63 ]. These results are supported by results of the present study which showed high antioxidant activity and high CAT levels in agreement with previous studies [ 30 , 63 , 64 ].…”
Section: Discussionsupporting
confidence: 94%
“…These chemobiological attributes mitigate the need for an amplified antioxidant network shield and redox-sensitive transcription factors, aiding in the restoration of the oxidant/antioxidant equilibrium. The increase in SOD, CAT, and GSH levels in the testis of UA-intoxicated rats following MLEE supplementation aligns with observations in rats affected by aluminum 61 and acrylamide 62 .…”
Section: Discussionsupporting
confidence: 84%
“…Our research also revealed that administering NaNO 2 reduced testosterone levels, indicating a disruption in steroidogenesis, this may be attributed to lower testicular StAR gene expression, proven in our gene expression analysis, which could have a role in inhibiting the synthesis of testosterone ( Mosbah et al ., 2018 ), cholesterol is transmitted to the inner mitochondrial membrane by the StAR, where it is converted by P450scc into pregnenolone, which is then converted into testosterone ( Miller, 2017 ).…”
Section: Discussionsupporting
confidence: 57%